Effect of printing angle and aging of a 3D-printed resin for provisional prostheses: an in vitro study on fracture resistance - Silva, Gabriela Marcele Lins da; Silva, Sandro Matheus Albuquerque da; Borba, Maria Terêza Lopes de Moura; Araujo, Adrielly Oliveira Soares de; Tôrres Neto, Antonio José; Barreto, Larissa Araújo Lopes; Lima Netto, Osman Jucá Rêgo de; Figueiredo, Viviane Maria Gonçalves de (Brazilian Dental Science, 2025)
Objective: The objective of this study is to evaluate the effect of printing angulation and aging on the fracture resistance of 3D-printed resin for provisional prostheses: an in vitro study. Material and Methods: Specimens of 3D-printed resin with dimensions of 25×2×2 mm were processed according to the manufacturer’s recommendations. Each experimental group consisted of n=5, categorized as follows: 0°, 45°, 90°, 0°A, 45°A, 90°A. Surface characterization was performed using scanning electron microscopy (SEM) (n=1). The specimens in groups 0°A, 45°A, and 90°A underwent aging in an incubator for 60 days at a temperature of 37 °C ± 0.5 °C in distilled water. All experimental groups were tested for three-point bending resistance using a universal testing machine, equipped with a 100 kgf load cell, set to a constant speed of 5 mm/min. Flexural strength values were recorded in megapascals (MPa). The mechanical strength data of the experimental groups were analyzed using a two-factor ANOVA test (p < 0.05) to assess the effects of printing angulation and aging. The findings from surface microscopy and fractography were qualitatively presented. Results: Distinct surface characteristics were identified in each experimental group, with the printed layers being more evident in the 45° and 90° angulations. A reduction in mean flexural strength values was observed for the 0° and 45° angulations after aging; however, no statistically significant differences were identified for the studied factors. The fractured specimens exhibited multiple fragments. Conclusion: Printing angulation and aging did not affect the mechanical performance of the 3D-printed resin for provisional prostheses. KEYWORDS Dental prosthesis; Digital technology; Flexural strength; Printing Angle; Three-dimensional printing.